2010
DOI: 10.3109/10428194.2010.483300
|View full text |Cite
|
Sign up to set email alerts
|

Primary hematolymphoid malignancies involving the extrahepatic bile duct or gallbladder

Abstract: Primary hematolymphoid malignancies of the extrahepatic biliary tract are rare tumors. We report five cases of primary hematolymphoid malignancies involving the extrahepatic biliary tract. One is a granulocytic sarcoma of the extrahepatic bile duct, another is an extramedullary plasmacytoma of the gallbladder, and the others are two non-Hodgkin lymphomas of the extrahepatic bile duct and one of the gallbladder. The clinical presentations, radiographic studies, and gross findings at surgery have not been a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Although various lymphoma subtypes have been reported in the literature, the most common subtype is large-cell lymphoma and the most common immunophenotype is B-cell lineage (12, 13). On the other hand, MALT lymphoma of the CBD is extremely rare, and our extensive review of the medical literature disclosed only four previously reported cases (3, 5-7). All four of these cases were elderly patients (age, 62-76 years) with an equal gender distribution.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although various lymphoma subtypes have been reported in the literature, the most common subtype is large-cell lymphoma and the most common immunophenotype is B-cell lineage (12, 13). On the other hand, MALT lymphoma of the CBD is extremely rare, and our extensive review of the medical literature disclosed only four previously reported cases (3, 5-7). All four of these cases were elderly patients (age, 62-76 years) with an equal gender distribution.…”
Section: Discussionmentioning
confidence: 88%
“…As with cholangiocarcinoma, the most common manifestation of the total 23 reported cases of primary CBD lymphoma is acute onset of obstructive jaundice with or without abdominal pain. However, as primary lymphoma accounts for less than 1% of all biliary obstructions and there is a general lack of familiarity with the diagnosis, primary lymphoma is seldom considered in the differential diagnosis (5, 12). Nonetheless, the dramatic difference in the prognosis and treatment of cholangiocarcinoma and primary lymphoma emphasizes the importance of the differential diagnosis in extrahepatic bile duct tumors with obstructive jaundice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such involvement may manifest similarly to primary cholangiocarcinoma, primary GB cancer or other common benign inflammatory, infectious, or obstructive diseases of the GB and biliary ducts [ 7 - 14 ]. Therefore, these extramedullary plasmacytomas are not typically considered in the differential diagnosis of biliary diseases, and the majority of cases are detected post-operatively or post-mortem [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date, only 5 cases reported in the English literature have described such tumors. [ 2 – 6 ] As reported by previous studies, differentiating between a MALT lymphoma of the hilar bile duct and a hilar cholangiocarcinoma (the most common form of bile duct cancer) is challenging.…”
Section: Discussionmentioning
confidence: 99%